2016
DOI: 10.1177/0031721716647023
|View full text |Cite
|
Sign up to set email alerts
|

Examining text complexity in the early grades

Abstract: The Common Core raises the stature of texts to new heights, creating a hubbub. The fuss is especially messy at the early grades, where children are expected to read more complex texts than in the past. But early-grades teachers have been given little actionable guidance about text complexity. The authors recently examined early-grades texts to discover what makes them complex and now report that there is a lot that can help teachers, specifically, young children’s texts are special, a handful of text character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Over the last 75 years of the century, they found, 3rd-grade texts actually showed a slight increase in complexity, not a decline. An analysis that attended only to texts for beginning readers showed that the increase in the complexity of texts for beginning readers was especially great from the 1960s to the mid-2010s (Fitzgerald et al, 2016). During that time, the number of challenge words in 1st-grade readers, which Jill Fitzgerald and colleagues (2016) defined as words that are predicted to occur after age seven in the oral-language environments of children, went from 1.5 per 1,000 words in 1962 to 46.9 per 1,000 words in the mid-2010s.…”
Section: New Insights From Researchmentioning
confidence: 99%
“…Over the last 75 years of the century, they found, 3rd-grade texts actually showed a slight increase in complexity, not a decline. An analysis that attended only to texts for beginning readers showed that the increase in the complexity of texts for beginning readers was especially great from the 1960s to the mid-2010s (Fitzgerald et al, 2016). During that time, the number of challenge words in 1st-grade readers, which Jill Fitzgerald and colleagues (2016) defined as words that are predicted to occur after age seven in the oral-language environments of children, went from 1.5 per 1,000 words in 1962 to 46.9 per 1,000 words in the mid-2010s.…”
Section: New Insights From Researchmentioning
confidence: 99%
“…Limited exposure of reading activities seems to be the contributing factors of this issue. The exposure itself can be influenced by various aspects such as age and years [1]. Such lack of exposure tend to cause low motivation in reading.…”
Section: Introductionmentioning
confidence: 99%